Determinants of Share Price Movement in Nigeria -The Management Perspective - Makinde, Hassan Olanrewaju (International Journal of Business, Economics and Management, 2015)
The study is motivated by the desire to investigate the determinants of share price movement given its fluctuation and oscillation over time. The study made use of secondary data sourced from the Central bank of Nigeria (CBN) and the National Bureau of Statistics (NBS) for period between 1991 and 2013. Using an appropriate analytical tool such as the ordinary least square (OLS) research technique; our study revealed that none of the selected factors have impacted positively on foreign portfolio investment in Nigeria except for market capitalization that was positive and statistically significant as well. Therefore, the study recommended that the on-going reform in the Nigerian capital market be sustained, especially in the area of investors’ protection and confidence, infrastructural development, and accounting disclosure requirements.